A forward-looking tracker of negotiated wages in the euro area: Eurosystem wage tracker experts - Lucyna Górnicka; Gerrit Koester (European Central Bank (ECB), 2024)
This paper introduces innovative, newly developed forward-looking indicators of negotiated wage growth in the euro area using data on collective bargaining agreements from seven countries: Germany, France, Italy, Spain, the Netherlands, Austria and Greece. The paper demonstrates how agreement-level data can be used to study drivers of aggregate negotiated wage growth, as well as monitor the breadth of wage increases and account for time-varying factors such as one-off payments, when assessing wage pressures. Lastly, the paper shows that the new indicators can provide reliable signals about current and future developments of wage pressures in the euro area while also serving as important cross-checking tools for negotiated wage growth forecasts.
Keywords: E24; J31; J50; 330; Negotiated wages; collective bargaining; wage rigidity; wage forecasting